Identification and Characterization of a New Serratia proteamaculans Strain That Naturally Produces Significant Amount of Extracellular Laccase - Ali, Nadia Sufdar; Huang, Fang; Qin, Wensheng; Yang, Trent Chunzhong (Frontiers in Microbiology, 2022)
Natural biodegradation processes hold promises for the conversion of agro-industrial lignocellulosic biomaterials into biofuels and fine chemicals through lignin-degrading enzymes. The high cost and low stability of these enzymes remain a significant challenge to economic lignocellulosic biomass conversion. Wood degrading microorganisms are great source for novel enzyme discoveries. In this study, decomposed wood samples were screened, and a promising γ - proteobacterial strain that naturally secreted significant amount of laccase enzyme was isolated and identified as Serratia proteamaculans AORB19 based on its phenotypic and genotypic characteristics. The laccase activities in culture medium of strain AORB19 was confirmed both qualitatively and quantitatively. Significant cultural parameters for laccase production under submerged conditions were identified following a one-factor-at-a-time methodology (OFAT): temperature 300C, pH 9, yeast extract (2g/l), Li+, Cu2+, Ca2+, Mn2+ (0.5mM) and acetone 5%. Under optimal conditions, a 6-fold increase (73.3 U/L) in laccase production was achieved when compared to the initial culturing conditions (12.18 U/L). Furthermore, laccase production was enhanced at alkaline and mesophilic growth conditions in the presence of metal ions and organic solvents. The results of the study suggests the promising potential of the identified strain and its enzymes in the valorization of lignocellulosic wastes. Further optimization of culturing conditions to enhance the AORB19 strain laccase secretion, identification and characterization of the purified enzyme and heterologous expression of the specific enzyme may lead to practical industrial applications.